The Fifty Most Cited Articles on Extra-articular Hip Pathology - Trofa, David P.; Swindell, Hasani W.; Mayeux, Sophie E.; Noticewala, Manish S.; Ahmad, Christopher S.; Lynch, T. Sean (The Journal of Hip Surgery, 2017)
The number of times an article has been cited is thought to correspond with its level of academic influence. Within the orthopaedic literature, several citation analyses have been performed, including a recent investigation on the most commonly cited articles on femoroacetabular impingement (FAI); however, no study has determined the most cited investigations on extracapsular hip pathologies, including osteitis pubis, athletic pubalgia, and muscle strains. Such pathologies constitute a significant proportion of lower extremity injuries among athletes. The purpose of this study was to determine the 50 most cited investigations on extra-articular hip injuries by performing a systematic query of the Institute for Scientific Information (ISI) Web of Science (Thomson Reuters, Philadelphia, PA). The following characteristics were determined for each article: number of citations, citation density, journal and publication year, country of origin, language, article type, article subtype, and level of evidence. The number of citations ranged from 46 to 202 (mean 84.4), and the citation densities ranged from 1.7 to 28.4 citations per year (mean: 7.9). Sixty-eight percent of the selected articles involved hamstring strains. The majority of articles were published in the American Journal of Sports Medicine (58%), followed by the Journal of Orthopaedic and Sports Physical Therapy (12%). Most articles were published during the 2000s, originated from the United States, and 100% were written in English. Eighty percent were clinical studies; the majority of which had Level IV evidence. This collection of academic investigations on athletic extra-articular hip injuries can aid in the establishment of a reading curriculum for trainees participating in orthopaedic training programs.
Keywords: citation analysis; osteitis pubis; athletic pubalgia; muscle strains